2016
DOI: 10.1186/s13054-016-1262-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of an algorithm to aid triage decisions for intensive care unit admission: a clinical vignette and retrospective cohort study

Abstract: BackgroundIntensive care unit (ICU) admission triage is performed routinely and is often based solely on clinical judgment, which could mask biases. A computerized algorithm to aid ICU triage decisions was developed to classify patients into the Society of Critical Care Medicine’s prioritization system. In this study, we sought to evaluate the reliability and validity of this algorithm.MethodsNine senior physicians evaluated forty clinical vignettes based on real patients. The reference standard was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…This finding differs from other studies, in which longer times for processes performed at night and on weekends were observed, explained by fewer staff in those periods. ( 8 - 11 ) However, the of vacancy-to-occupancy time increased when the bed was offered on holidays, in line with the cited studies.…”
Section: Discussionsupporting
confidence: 73%
“…This finding differs from other studies, in which longer times for processes performed at night and on weekends were observed, explained by fewer staff in those periods. ( 8 - 11 ) However, the of vacancy-to-occupancy time increased when the bed was offered on holidays, in line with the cited studies.…”
Section: Discussionsupporting
confidence: 73%
“…A possible explanation for this is the scarcity of ICU beds in the SUS, leading the hospitals to use screening criteria to admit patients to ICU beds 22. Since most of these triage tools used age-related comorbidities (eg, cancer and decompensated chronic diseases) and functionality status to prioritise patients for ICU admission, it is expected that older patients, especially the very older (≥80 years), will receive a lower priority than younger patients 23.…”
Section: Discussionmentioning
confidence: 99%
“…In our study higher accuracy in prediction is likely explained by the fact that physicians estimated survival for patients they had actually assessed. We could not compare physicians’ performance with a scoring system as no validated score exists for estimating patient prognosis at the time of triage [ 10 , 11 ]. However, physicians’ clinical judgment has been shown to be at least as accurate as objective risk scores for predicting mortality in patients admitted to the ICU [ 5 ] and for predicting medical in-patients’ deterioration [ 12 ].…”
Section: Discussionmentioning
confidence: 99%